The rehabilitation workforce in Brazil - Taciana Rocha dos Santos Sixel; Debora Bernardo; Arthur de Almeida Medeiros; Aylene Bousquat; Paulo Henrique dos Santos Mota; Ana Carolina Basso Schmitt (BMC, 2024)
Abstract Background The surge in individuals facing functional impairments has heightened the demand for rehabilitation services. Understanding the distribution of the rehabilitation workforce is pivotal for effective health system planning to address the population's health needs. Objective To investigate the spatial and temporal dispersion of physical therapists, speech therapists, psychologists and occupational therapists across various tiers of care within Brazil's Unified Health System and its regions. Method This is an ecological time series study on the supply of rehabilitation professionals. Data were obtained from the National Register of Health Establishments from 2007 to 2020. The density of professionals was calculated per 10,000 inhabitants annually for Brazil and its five regions. The Joinpoint regression model was used to analyze the temporal trends of the density of professionals, considering a 95% confidence interval. Results In 2020, the most notable concentrations of psychologists, speech therapists, and occupational therapists in Brazil were observed in the domain of Specialized Health Care, with densities of 0.60, 0.20, and 0.16 professionals per 10,000 inhabitants, respectively. Conversely, the highest density of physical therapists was found within Hospital Health Care, with a density of 1.19 professionals per 10,000 inhabitants. Notably, variations in professional dispersion across different regions were apparent. Primary Health Care exhibited the highest density of professionals in the Northeast region, while the Southern region accounted for the highest densities in all professional categories within Specialized Health Care. The southeast region exhibited the largest workforce within Hospital Health Care. A marked upsurge in professional availability was noted across all categories, notably in the occupational therapy sector within hospital care (AAPC: 30.8), despite its initial low density. Conclusion The implementation of public health policies played a significant role in the expansion of the rehabilitation workforce at all three levels of care in Brazil and its various regions from 2007 to 2020. Consequently, regional disparities and densities of professionals have emerged, mirroring patterns observed in low-income countries.